2014
DOI: 10.3945/jn.114.197624
|View full text |Cite
|
Sign up to set email alerts
|

Diets High in Protein or Saturated Fat Do Not Affect Insulin Sensitivity or Plasma Concentrations of Lipids and Lipoproteins in Overweight and Obese Adults

Abstract: These findings suggest that short-term intake of BCAAs can influence insulin dynamics. However, in this group of overweight and obese individuals, neither high protein nor SF intake affected insulin sensitivity or plasma concentrations of lipids and lipoproteins. This trial was registered at clinicaltrials.gov as NCT00508937.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 68 publications
5
32
0
Order By: Relevance
“…Although the amounts consumed in these studies were higher than Australian National Health and Medical Research Council dietary guidelines, which recommend 2.5 servings of dairy each day (24), typical intake in Australia is ,2 servings/d (25). Our data were partly consistent with that of Chiu et al (26) who showed, in a large study, that increasing predominantly dairy fat and dairy protein did not improve insulin sensitivity. Although no impairment of insulin sensitivity was shown, dairy branched-chain amino acids (BCAAs) were related to fasting insulin concentrations and insulin clearance.…”
Section: Discussionsupporting
confidence: 82%
“…Although the amounts consumed in these studies were higher than Australian National Health and Medical Research Council dietary guidelines, which recommend 2.5 servings of dairy each day (24), typical intake in Australia is ,2 servings/d (25). Our data were partly consistent with that of Chiu et al (26) who showed, in a large study, that increasing predominantly dairy fat and dairy protein did not improve insulin sensitivity. Although no impairment of insulin sensitivity was shown, dairy branched-chain amino acids (BCAAs) were related to fasting insulin concentrations and insulin clearance.…”
Section: Discussionsupporting
confidence: 82%
“…In animal models an increase in intracellular fatty acyl-CoA and diacylglycerol concentrations decreased insulin-stimulated glucose transport activity by inhibiting insulin activation of insulin receptor substrate-1 (IRS-1) and phosphatidylinositol 3-kinase (PI3K) activity [35]. In a recent large sample of overweight and obese adults [36], SFAs did not affect insulin sensitivity assessed by FSIGT. One hundred and fifty eight adults underwent a 4-week baseline diet [55%E carbohydrate, 15%E protein, 30%E fat (7% E saturated fat (SF)] and were then randomized to 4 weeks of either the baseline diet or 1 of 4 test diets containing 35% E carbohydrate and either 20%E or 30%E protein and either 7%E or 15%E SF mostly from dairy.…”
Section: Referencementioning
confidence: 98%
“…The present study demonstrated that the substitution of ω-6 PUFAs for SFAs has no beneficial effects on TRL apoB-48 kinetics and postprandial lipemia in subjects with dyslipidemia associated with IR. Accordingly, accumulating evidence now suggests that the impact of dietary fat on postprandial lipoprotein metabolism and CVD risk factors is attenuated by IR (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%